Properties of the legislation of Kazakhstan and Russia in the development of information policy and security - Pernebekova, А.П. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2021)
The article examines the laws on information security and information policy in Kazakhstan and Russia. There is relatively shown information political situation of the two countries. The authors comprehensively analyzed interests of the two states in the information sphere, implementation of basic information rights and freedoms of citizens, development of competitive information tools, information and telecommunications industry, application and creation of information technologies, development of information products and services, state policy in the field of information security, international cooperation in the information sphere. In general, as the process of informatization of society intensively develops and enters the world information space along with its profits, the negative aspects naturally increase. The influence of mass culture can lead to the subsequent displacement of national culture. After all, in any form of media you can find a lot of information that is alien to our national culture, our teachings. The dynamics of the development of information technology, which occupies a significant place in the political-economic and socio-cultural life of the state, places high demands on the solution of the problems of information security. Information policy in the state regulates the activities of information institutions aimed at the development of the information sphere of society. This method includes not only the press but also the totality of all productions and connections in the form of television and radio connections, creation, storage, processing, display of information systems and web resources, distribution of information from entertainment to science, politics, etc. The information policy of the state makes sure that the organizational forms in the media are diverse and equitable; the actualization of the public task of the mass media; impartiality of the information policy of national, regional, and local authorities. All these issues are the main issues in the article.